If We Do It Right, It Will Hurt: The Official Languages Act, Nation-Building, and English-Speaking Quebec - Sandilands, Marion (Minorités linguistiques et société / Linguistic Minorities and Society, 2021)
In Quebec—a province with complex and fraught language politics—the federal Official Languages Act recognizes the English-speaking population of Quebec as a minority language community. Anchored in the perspective of English-speaking Quebec, the essay argues that the Official Languages Act is an attempt at nation-building, embedded and embroiled in the history and politics of language. First, the essay discusses how the existence of English-speaking Quebec shaped language rights and the Official Languages Act in particular. Next, it describes the English-speaking minority of Quebec and how this minority fits within the framework of the Act, commenting on and critiquing the Act from this perspective. Lastly, it argues that the modernization of the Act is more than just a technical exercise and that it requires a national conversation and debate around language and identity.